Imperialisme Gaya Baru Terhadap Buruh Industri Garmen di Bangladesh dalam Kerangka Modern World System - Sukma Ayu Putri (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2021)
Exploitation of labour has been big problems in Bangladesh, its combination between imperialist (thats the US and European Garment Consortium), local factory owners and government. Dependence Bangladesh as a periphery country under fashion companies from core country is the evidence of existing modern world system. This paper discusses about how exploitation and poverty correlate with development failures in Bangladesh. Actually, working in the garment industry are the another way to reach their basic needs, but in fact, they all getting low salary which is under minimum cost of living. Until now, the ready-made garments (RMG) industry of Bangladesh still being